Immunological outcomes after six months with first line antiretroviral therapy: a lesson from Yogyakarta, Indonesia - Mardy Pangarungan; Eggi Arguni (Journal of Infection in Developing Countries)
Introduction: More than 1,300 children aged 0-14 years were infected with HIV in Indonesia by 2016. Adequate antiretroviral therapy (ART) can increase nutritional and immunological status, reduce incidence of opportunistic infection and mortality caused by HIV infection. After ART initiation, the children’s treatment response needs to be monitored with CD4+ cell count and Viral Load (VL) evaluation. In resource-limited setting, clinical and immunological parameters can be used to evaluate ART outcomes. The aimed of this study to know immunological status of the patient after 6 months ART in Dr. Sardjito Hospital in Yogyakarta, Indonesia.